Building a Modern Organization: Transforming from Mechanical to Organic Structure in Marketing Teams - Hartono Ginting (International Journal of Economics, Management and Accounting, 2024)
The transformation of organizational structure from mechanical to organic form is a strategic step in adapting to rapid changes in the business environment, especially in the marketing function. This study aims to examine the process and challenges in this transformation using a qualitative approach. The study was conducted on five companies in the technology and consumer product sectors that have adopted organic structures in their marketing teams. The results of the study indicate that organic structures increase market responsiveness, cross-functional collaboration, and team creativity, but require strong leadership, supporting technology, and changes in organizational culture. These findings provide important insights for the development of more adaptive and innovative modern organizations.